2012
DOI: 10.1007/s11356-012-1045-3
|View full text |Cite
|
Sign up to set email alerts
|

Silver behaviour along the salinity gradient of the Gironde Estuary

Abstract: Dissolved and particulate Ag concentrations (Ag(D) and Ag(P), respectively) were measured in surface water and suspended particulate matter (SPM) along the salinity gradient of the Gironde Estuary, South West France, during three cruises (2008-2009) covering contrasting hydrological conditions, i.e. two cruises during intermediate and one during high freshwater discharge (~740 and ~2,300 m(3)/s). Silver distribution reflected non-conservative behaviour with 60-70 % of Ag(P) in freshwater particles being desorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 55 publications
(104 reference statements)
1
1
0
Order By: Relevance
“…This is in agreement with the fact that the Gironde Estuary is a historically Cd-contaminated ecosystem (Durrieu et al, 2005). Moreover, recent studies have reported high levels of Ag in surface water and suspended particulate matter along the Gironde Estuary (Lanceleur et al, 2013). In contrast to non-essential metals, essential metals such as copper (Cu), selenium (Se) and zinc (Zn) showed significant lower levels in gonads from Gironde compared to Certes.…”
Section: Gsi and Pollutant Bioaccumulationsupporting
confidence: 85%
“…This is in agreement with the fact that the Gironde Estuary is a historically Cd-contaminated ecosystem (Durrieu et al, 2005). Moreover, recent studies have reported high levels of Ag in surface water and suspended particulate matter along the Gironde Estuary (Lanceleur et al, 2013). In contrast to non-essential metals, essential metals such as copper (Cu), selenium (Se) and zinc (Zn) showed significant lower levels in gonads from Gironde compared to Certes.…”
Section: Gsi and Pollutant Bioaccumulationsupporting
confidence: 85%
“…Paraguaçu estuaries in Brazil (around 15 ng/L;Andrade et al, 2020) or the Pearl River estuary in China (around 60 ng/L;Ma et al, 2019). In the case of Ag, these values are higher than those previously reported in most European estuaries(Tappin et al, 2010), some of them affected by mining and agriculture activities such as the Fal and Tamar estuaries in UK (2.0 and 3.7 ng/L;Tappin et al, 2010) and the Restronguet Creek (19 ng/L;Tappin et al, 2010) and Gironde estuaries (6-8 ng/L,Lanceleur et al, 2012) in France. On the contrary, values recently reported byRibeiro et al (2018) in the Portuguese Douro estuary (i.e.…”
mentioning
confidence: 73%
“…In addition, the regular re-suspension of sediment and the salinity gradient can induce remobilization of contaminants (Lanceleur et al 2013).…”
Section: Introductionmentioning
confidence: 99%